Digital Life Insurance- A Post Covid Agenda - Bedi, Ridhima (Gyan Management Journal, 2023)
Covid19 outbreak has not spared any sector. The entire Service sector  was majorly impacted by this deadly virus. But Life Insurance was one of  the sectors which benefited in this period. Digital services are the need of  the time. Technology has become the backbone of every service industry  and Insurance enhanced their services in the post covid era. Though the  Insurance Industry was one of the quickest to adopt technology in the  services but left itself behind with its updating. Insurance provides not just  security but also encourages savings and provides long term funds with  overall economic growth. This paper focuses on the extensive literature  review of digital trends in the life insurance sectors and the hinderance  faced by the life Insurance sector in digital adoption post covid. The  results of the study showed the need of digital insurance in the rural areas  as well as its importance in the untapped areas as Insurance penetration  is not at its peak yet despite of all the years in this business. The study also  shows various hurdles faced by the life insurance industry in the digital  adoption with various suggestions to coop-up with the current tech era.
Keywords: Digital Technology; Life Insurance; Trends; Digital Insurance